Developing a Web Based Sales Monitoring and Forecasting System for Digital Transformation of Rural MSMEs - Arief, Murahartawaty; Azzahra, Zalina Fatimah; Panduwiyasa, Haryasena; Lijona, Lijona; Sawardi, Stefanus Arda; Pratama, Reza Herdianto (Jurnal Pustaka Robot Sister (Jurnal Pusat Akses Kajian Robotika, Sistem Tertanam, dan Sistem Terdistribusi), 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face significant hurdles in digital adoption, with only 30% to 32% currently utilizing digital management tools. To address this challenge, this research focuses on Dapur Ovaltin, an agribusiness MSMEs in Ciwidey, West Java, that previously relied entirely on manual sales recording. The primary objective of this study is to design and implement a web-based monitoring and forecasting system to enhance operational efficiency. Developed through a hybrid framework integrating Design Thinking and the Prototyping SDLC, the resulting application streamlines sales management and applies Simple Linear Regression to transactional data for precise inventory forecasting. This implementation yielded a comprehensive platform featuring digital product catalogs, transaction management, and interactive data visualization. Ultimately, the deployed system successfully transformed manual operations into a cohesive digital process, replacing fragmented logs with a centralized database that empowers data-driven decision-making for sustainable enterprise growth.